The systemic changes to improve efficiency in Polish Primary Health Care - Tomasz Holecki; Piotr Romaniuk; Joanna Woźniak-Holecka (Frontiers Media S.A., 2016)
Primary health care is an important part of any health care system. In highly developed countries it secures the population's most elementary health needs, with particular emphasis on preventive care and early intervention. Polish PHC model is currently undergoing a thorough transformation, associated with the need to adapt to standards designated based on the WHO's criteria, and with reference to the experience of other European countries. The paper describes the process of changes being carried out, in the context of previous experiences of reform relating to the sphere of organization, processes and efficiency. A review and systematization has been made, with regard to the undertaken activities in the field of deregulation and change of legal provisions, which are aimed at achieving the improvement of the efficiency of treatment and resource allocation. A set of recommendations based on expert's discourse have also been provided, with respect to future directions of Polish PHC transformation.